The star of Bethlehem : [videorecording (DVD)] : unlock the mystery of the world's most famous star - Vidano, Stephen; Larson, Frederick A. (Genius Entertainment, 2007)
A look at the Biblical account of the Star, how the Bible recounts unusual and even impossible astronomical events at Christ's birth, and how it's a mystery based on faith.